Awerroistyczna doktryna podwójnej prawdy. Próba rozdzielenia sfer sacrum i profanum na gruncie filozofii przyrody - Kokoć, Damian (Polskie Towarzystwo Religioznawcze, 2012)
Damian Kokoć – AVERROES'S DOCTRINE OF DOUBLE TRUTH. AN ATTEMPT OF DIVISION OF THE SACRED AND PROFANE ON THE BASIS OF PHILOSOPHY OF NATURE The proposed by Averroes and accepted and developed by his Latin followers doctrine of double truth is one of the first attempts of giving autonomy to scientific cognition in relation to the theological field. Thinkers from this intellectual current have noticed, that we deal here with two independent cognitive orders. The order of faith, which as its objective takes the sacred, what is trans-cendent and what includes in its remarks the possibility of intervention of God in the world; an intervention, which is able to cause in the material reality a phenomenon contardictory to the laws ruling it. The other is the order of scientific cognition, in which one disregards the sacred. In this order one omits what is supernatural and focuses solely on what is cognitive and available to our senses and reason.